Feasibility randomized‐controlled trial of online acceptance and commitment therapy for painful peripheral neuropathy in people living with HIV: The OPEN study. (26th March 2021) - Scott, Whitney; Guildford, Beth J.; Badenoch, James; Driscoll, Elizabeth; Chilcot, Joseph; Norton, Sam; Kemp, Harriet I.; Lee, Ming J.; Lwanga, Julianne; Boffito, Marta; Moyle, Graeme; Post, Frank A.; et al.
Abstract: Background: Neuropathic pain negatively affects quality of life among people living with HIV (PLWH). This study examined the feasibility of conducting a full‐scale randomized‐controlled trial of online acceptance and commitment therapy ("ACT OPEN") for neuropathic pain in PLWH. Methods: Using a parallel‐groups design, thirty‐eight participants were randomized to ACT OPEN or a waitlist control (2:1). Participants completed standard self‐report outcome measures at baseline, and two‐ and five‐months post‐randomization. Participants were aware of their allocation, but assessment was blinded. Results: Twenty‐five participants were randomized to ACT OPEN and 13 to the control (of 133 referrals). ACT OPEN completion was 69% and two‐month trial retention was 82%. Treatment credibility and satisfaction scores for ACT OPEN were comparable to scores reported in previous trials of cognitive‐behavioural treatments for pain. Four adverse events were reported during the study, including one serious adverse event; all of these were unrelated to the research procedures. Small to moderate effects and 95% confidence intervals suggest that the true effect may favour ACT OPEN for improvements in pain intensity/interference and depression. Conclusions: A full‐scale RCT of online ACT for pain management in PLWH may be feasible with refinements to trial design to facilitate recruitment. Significance: Research on pain management in people living with HIV has primarily focused on pharmacological treatments with limited success. This is the first study to show the potential feasibility of a psychological treatment based on acceptance and commitment therapy delivered online and tailored for pain management in people with HIV ("ACT OPEN"). ACT OPEN may be a promising treatment in this population and further evaluation in a full‐scale randomized‐controlled trial appears warranted. Trial Registration: The trial was registered (clinicaltrials.gov; NCT03584412).